Ore-geochemical zonality and gold complex potential of Muruntau - Ezhkov Yu.B.; Rakhimov R.R.; Rustamjonov R.R.; Novikova I.V. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2017)
This work considers features of genesis, a deep structure and a prospective value of the Muruntau ore field and its flanks, a spatial relation of various classes of gold ores in the operational condition, changes of an industrial ore concentration of gold through time and conditions of its production from technogenic sources. Allocated in the Central Tamdytau on zones of a real ore content (Hg, Au, Ag), to geochemical anomalies (to Ag, Au, W, Hg, Sb, As) and to thin-section blue cap of gold, a scheelite, cinnabarite, diaspore, etc., the expected and search area is estimated as the indicator of the covered and bridged over large-scale gold complex of ore grade mineralization.
Keywords: MURUNTAU; ORE FIELD; GOLD ZONE; GEOLOGICAL-GENETIC MODEL; TAMDYTAU; GEOCHEMICAL ZONALITY; AU; AG; SB; AS; W; CU; SN